2020
DOI: 10.1080/15592324.2020.1714189
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis mtHSC70-1 physically interacts with the Cox2 subunit of cytochrome c oxidase

Abstract: The 70-kD heat shock proteins (HSP70s or HSC70s) function as molecular chaperones and are involved in diverse cellular processes. We recently demonstrated the roles of mitochondrial HSC70-1 (mtHSC70-1) in the establishment of cytochrome c oxidase (COX)-dependent respiration and redox homeostasis in Arabidopsis thaliana. Defects in COX assembly were observed in the mtHSC70-1 knockout lines. The levels of Cox2 (COX subunit 2) proteins in COX complex were markedly lower in the mutants than in wild-type plants; ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Our previous results [ 47 , 48 ] and the data presented here support a working model in which mtHSC70-1 acts to assist respiratory chain complex IV assembly/activity and regulate ROS homeostasis, which maintains normal PAT and regulates plant growth and development ( Figure 11 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our previous results [ 47 , 48 ] and the data presented here support a working model in which mtHSC70-1 acts to assist respiratory chain complex IV assembly/activity and regulate ROS homeostasis, which maintains normal PAT and regulates plant growth and development ( Figure 11 ).…”
Section: Discussionsupporting
confidence: 83%
“…A. thaliana mtHSC70-1 has weak ATPase activity, which is stimulated by mitochondrial J-domain protein AtDjB1 [ 46 ]. Wei et al [ 47 ] and Zhai et al [ 48 ] reported that A. thaliana mtHSC70-1 knockout leads to severe growth inhibition and an increase in mitochondrial ROS levels during the vegetative growth of plants and that mtHSC70-1 is directly involved in respiratory chain complex IV/cytochrome c oxidase (COX) assembly and the establishment of COX-dependent respiration. Li et al [ 49 ] reported that A. thaliana mtHSC70-1 knockout impairs embryo development, and this effect is mediated by auxin.…”
Section: Introductionmentioning
confidence: 99%
“…et al 2020. [ 22 ] ZmHsf05 Zea mays ZmHsf05 plays an important role in both basal and acquired temperature tolerance in plants. Li GL.et al 2019 [ 23 ] ZmHsf01 Zea mays Lines overexpressing ZmHsf01 showed higher chlorophyll content and survival rate after HS Zhang H. et al 2020 [ 24 ] ZmHsf17 Zea mays Binds to the promoter of small heat shock proteins Qi H. et al 2022 [ 25 ].…”
Section: Resultsmentioning
confidence: 99%